La industria cultural en el mundo. Estructura, composición y distribución territorial de los grupos multimedia en España - Agustín Gámir Orueta (Cybergeo, 2004)
The aim of this paper consists in clarifying the main attributes of the cultural industry and also to show the panorama of this industry in Spain. For that propose the elements that define the cultural industry will be pointed in the context, not of Cultural Geography but of Economic Geography. We shall put the emphasis on the economic weight of the language as an essential input of this kind of industry. Also, the main companies of the sector will be identified, as well as their process of horizontal and vertical integration and their interrelation with other economic sectors. The paper pays attention to the role of multimedia companies in the development of cultural identity for the territories, and the deal of the cultural goods in the international organizations. At this point a thematic and spatial approach has been achieved, so that we can actually describe the main territorial distribution of the Spanish cultural industry, the multimedia groups, their internal structure and their spatial patterns in Spain.